2023
DOI: 10.1002/cl2.1339
|View full text |Cite
|
Sign up to set email alerts
|

The effects of flipped classrooms to improve learning outcomes in undergraduate health professional education: A systematic review

Abstract: BackgroundThe ‘flipped classroom’ approach is an innovative approach in educational delivery systems. In a typical flipped class model, work that is typically done as homework in the didactic model is interactively undertaken in the class with the guidance of the teacher, whereas listening to a lecture or watching course‐related videos is undertaken at home. The essence of a flipped classroom is that the activities carried out during traditional class time and self‐study time are reversed or ‘flipped’.Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 152 publications
(472 reference statements)
1
4
0
Order By: Relevance
“…In addition, Akçayır and Akçayır 39 reported that the most common benefit associated with a flipped classroom approach was the enhancement of student learning performance. These findings align with the results of Naing et al, 41 who also concluded that the implementation of flipped classrooms has the potential to improve academic achievement and enhance student satisfaction across various health professional programs. Although our study did not specifically assess students' learning performance in terms of EBP knowledge, skills, and attitudes, most participants (90.5%) reported a positive perception of the overall learning outcome on the Likert scale in the evaluation survey.…”
Section: Health Claims As An Entry Point For Ebpsupporting
confidence: 90%
“…In addition, Akçayır and Akçayır 39 reported that the most common benefit associated with a flipped classroom approach was the enhancement of student learning performance. These findings align with the results of Naing et al, 41 who also concluded that the implementation of flipped classrooms has the potential to improve academic achievement and enhance student satisfaction across various health professional programs. Although our study did not specifically assess students' learning performance in terms of EBP knowledge, skills, and attitudes, most participants (90.5%) reported a positive perception of the overall learning outcome on the Likert scale in the evaluation survey.…”
Section: Health Claims As An Entry Point For Ebpsupporting
confidence: 90%
“…It is generally accepted that active learning increases student academic performance in science ( Freeman et al, 2014 ). Teaching paradigms that promote active learning, such as FC, have long been advocated to cope with various drawbacks affecting the traditional educational environment ( Naing et al, 2023 ). This is particularly evident in undergraduate classrooms with large number of students who easily choose to skip classes and concentrate on studying for final examinations that usually maximize evaluation of facts and short-memory retention.…”
Section: Discussionmentioning
confidence: 99%
“…Many conflicting reports are available about the effects of FC systems on final examination scores ( Chen et al, 2018 ; Gopalan, 2019 ; Barranquero-Herbosa et al, 2022 ; Naing et al, 2023 ). A prospective randomized controlled study finds FC positive effect on grades ( Anderson et al, 2017 ), and a study in advanced Physiology also finds statistically significant improvements in final grades ( Rathner and Schier, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, most of the studies have reviewed the literature on flipped classrooms qualitatively (Chen et al, 2021;Barranquero-Herbosa et al, 2022;Naing et al, 2023) and lack an objective description of the status of flipped classrooms research. To elucidate the situation of flipped classrooms as a new educational model in different disciplines, it is necessary to understand better the overall landscape of flipped classroom-related research and future trends (e.g., applied disciplines, applicable population).…”
Section: Introductionmentioning
confidence: 99%